Length‐weight relationships of five Triplophysa species from the northwest of China. (21st July 2017) - Chen, S.; Xie, C.; Li, D.; Yao, N.; Ding, H.; Zhang, Z.
Summary: Length‐weight relationships were estimated for five Triplophysa species from the northwest China. A total of 1, 598 specimens were collected using set gillnets (mesh size 1.5 cm) and ground bamboo cages in May 2012, and August 2014. This study presents the first references on LWRs for Triplophysa minuta, T. siluroides, and T. tenuis, and two new maximum length records for T. yarkandensis and T. strauchii . Statistical length–weight relationships for all five species were highly significant ( p  < .001), with R 2 values >.915.